2019
DOI: 10.1021/acs.jmedchem.9b00812
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Affinity Relationships of 2,3,4,5-Tetrahydro-1H-3-benzazepine and 6,7,8,9-Tetrahydro-5H-benzo[7]annulen-7-amine Analogues and the Discovery of a Radiofluorinated 2,3,4,5-Tetrahydro-1H-3-benzazepine Congener for Imaging GluN2B Subunit-Containing N-Methyl-d-aspartate Receptors

Abstract: Aspiring to develop a positron emission tomography (PET) imaging agent for the GluN2B subunits of the N-methyl-d-aspartate receptor (NMDAR), a key therapeutic target for drug development toward several neurological disorders, we synthesized a series of 2,3,4,5-tetrahydro-1H-3-benzazepine and 6,7,8,9-tetrahydro-5H-benzo­[7]­annulen-7-amine analogues. After in vitro testing via competition binding assay and autoradiography, [18F]­PF-NB1 emerged as the best performing tracer with respect to specificity and select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 67 publications
3
22
0
Order By: Relevance
“…At the time, it was also reported that 3-(4-phenylbutyl)-2,3,4,5-tetrahydro-1H-benzazepine-1,7-diol exhibits 18-fold higher GluN2B subunit affinity than its methoxy analog (15). Remarkably, we showed in our previous study that the loss of high binding affinity and selectivity of the para-fluorinated 3-benzazepin-1ol (PF-Me-NB1) could be restored on cleavage of the methyl ether group (16). More importantly, we found that the (S)-and (R)enantiomers of PF-NB1 did not differ in their in vitro properties with regard to their binding affinity and selectivity toward GluN2B subunits.…”
mentioning
confidence: 55%
See 3 more Smart Citations
“…At the time, it was also reported that 3-(4-phenylbutyl)-2,3,4,5-tetrahydro-1H-benzazepine-1,7-diol exhibits 18-fold higher GluN2B subunit affinity than its methoxy analog (15). Remarkably, we showed in our previous study that the loss of high binding affinity and selectivity of the para-fluorinated 3-benzazepin-1ol (PF-Me-NB1) could be restored on cleavage of the methyl ether group (16). More importantly, we found that the (S)-and (R)enantiomers of PF-NB1 did not differ in their in vitro properties with regard to their binding affinity and selectivity toward GluN2B subunits.…”
mentioning
confidence: 55%
“…Chemicals and materials were purchased from ABCR, Ametek Scientific, Armar, Merck, Sigma-Aldrich, Acros Organics, and PerkinElmer and were used directly without any further purification. Detection, characterization, and binding affinity experiments were performed in accordance with previously published procedures (16).…”
Section: Chemistry and Binding Affinity Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Seeking to develop a fluorine-18 labelled analogue of [ 11 C]Me-NB1 due to the inherently brief physical half-life of carbon-11, which limits its use only to centers with an on-site cyclotron, the Ametamey group evaluated a series of fluorinated analogues of Me-NB1 [ 74 , 75 , 76 ]. Two fluorine-18 labelled compounds, [ 18 F]OF-NB1 ( 42b ) and [ 18 F]PF-NB1) ( 42c ) ( Figure 4 ) emerged as promising radioligands for imaging the GluN2B receptor.…”
Section: Glutamate Receptorsmentioning
confidence: 99%